Analisis Nilai Efektivitas pada Mesin Gas Cutting Koike Sanso Kogyo Type IK-2000 CE HI-82 dengan Metode Overall Equipment Effectiveness (OEE) pada Perusahaan Manufaktur Alat Transportasi - Devianti Kusuma Hardinata; Renanda Nia Rachmadita; Aditya Maharani (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
This manufacturing company is one of the BUMN that moved in transportation. This company produce train-sets and and single-parts. The material will be processed into cutting area by using automatic gas cutting machine, it is Koike Sanso Kogyo type IK 2000 CE HI-82. This machine operates in 3 shifts during 24 hours and in over time. As thi smachine is used continuously and it is used to reach target of products, so it somestimes happens ome failures from the machine and because of the failures, it takes more time to repair or controlit. Overall Equipment Effectiveness (OEE)isone of method that used to identify the value of effectivity of the equipment and to evaluate the performance of the machine. For some failures that somestimes happen in this machine will be analyzed by using Failure Mode and Effect Analysis (FMEA). All of the types failures that happen will be handled based on priority order by using Risk Priority Number (RPN). The priorities order of each failures will be found the root cause by using Fault Tree Analysis(FTA). Overall Equipment Effectiveness (OEE) used to repair the productivity of the company and used as a decision step. From all of the processing data step, the value of the Overall Equipmen tEffectiveness (OEE) on 2017 is 57,34%,with the dominan factor that influence is performance rate with the value 79,42%. Some alternative solutions that can be taken are machine daily checklist ,machine monthly checklist, and operators training.